(untitled) (BIBECHANA, 2024)
Among the natural disasters, landslides, flood, thunderstorm, fire, are major destructive disaster. In every season, fire is the main cause of the death of the people which frequently occurred in spring and winter seasons. The landslide seems to be very destructive in the summer season, flood is also in the summer season, and thunderbolt occurs frequently in spring and summer seasons (pre-monsoon period). The different disaster occurred in different season frequently and have more effect on human, animals, and huge loss of property due to it. Due to the geographical structure of our scenario, the destruction seems to be high in Nepal. Hence, the disasters can’t be stopped, but can be reduced and awareness program should be conducted to mitigate its effects.